Hubungan Usia, Lama Melaut, Asupan Natrium, dan Kalium dengan Kejadian Hipertensi pada Nelayan di Desa Blimbing, Paciran Lamongan - Muhammad andy Dwi Purnomo; Siti Rahayu Nadhiroh; Qonita Rachmah (Universitas Airlangga, 2023)
Background: Hypertension on fishermen is a health problem characterized by blood pressure of over 140/90 mmHg. Hypertension conditions if not treated appropriately could result in complications of stroke, myocardium infarction, kidney failure, brain damage, blindness, to death in fishermen. Objectives: In order to get a typical profile and analyze their sodium and potassium intake links with the incidence of hypertension in the village of blimbing, Paciran, Lamongan 2022. Methods: The study is a descriptive analysis study that uses primary data with fishing populations in the village area of blimbing, the crop district. This research data retrieval technique through interviews of respondents and the sample retrieval technique used was from a total sample of 41 fishermen. Data analysis uses a chi-square correlation test. Results: The study shows that the characteristics of fishermen reach an average age >40 years, an average length of time of 11 days, and an average history of fishing for 18 years. The incidence of hypertension in fishermen is 58.5% and 22% have a history of hypertension. Fishermen with high levels of potassium (>3000 mg) rise to 78% and fishermen with excess sodium intake (>2300 mg) to 49% of the population sample. Statistical analysis shows that at age variables and a history of working in connection with the incidence of hypertension in fisherman blimbing village has a value of p-value. Conclusions: Based on the study it may be concluded that the incidence of hypertension in the village of blimbing is affected by the age of those who responded to and long fishing that took place over the years and is most likely to change their eating habits on land.